Effects of climate legacies on above‐ and belowground community assembly. (30th May 2018) - Delgado‐Baquerizo, Manuel; Eldridge, David J.; Travers, Samantha K.; Val, James; Oliver, Ian; Bissett, Andrew
Abstract: The role of climatic legacies in regulating community assembly of above‐ and belowground species in terrestrial ecosystems remains largely unexplored and poorly understood. Here, we report on two separate regional and continental empirical studies, including >500 locations, aiming to identify the relative importance of climatic legacies (climatic anomaly over the last 20, 000 years) compared to current climates in predicting the relative abundance of ecological clusters formed by species strongly co‐occurring within two independent above‐ and belowground networks. Climatic legacies explained a significant portion of the variation in the current community assembly of terrestrial ecosystems (up to 15.4%) that could not be accounted for by current climate, soil properties, and management. Changes in the relative abundance of ecological clusters linked to climatic legacies (e.g., past temperature) showed the potential to indirectly alter other clusters, suggesting cascading effects. Our work illustrates the role of climatic legacies in regulating ecosystem community assembly and provides further insights into possible winner and loser community assemblies under global change scenarios. Abstract : The role of climatic legacies in regulating community assembly of above‐ and belowground species in terrestrial ecosystems remains poorly understood. Here, we report on two separate regional and continental empirical studies, including >500 locations, aiming to identify the relative importance of climatic legacies (climatic anomaly over the last 20, 000 years) compared to current climates in predicting the relative abundance of ecological clusters within two independent above‐ and belowground networks. Our work illustrates the role of climatic legacies in regulating ecosystem community assembly and provides further insights into possible winner and loser community assemblies under global change scenarios.